Pragmatic Competence Of Indonesian EFL (English Foreign Language) Learners In Understanding Grammar And Pragmatic Error - Cahyani, Emma Febri; , Agus Wijayanto, Ph.D; , Dra. Malikatul Laila, M. Hum (2014)
This study analyzed pragmatic competence of Indonesian EFL (English Foreign Language) learners. This research also identify whether the length of study influence the learners in comprehension of grammar and pragmatic errors. The type of this research was qualitative analysis. The researcher focused on analyzing the comprehension of grammar and pragmatic errors. The objective of this research is to know the understanding of students relating grammar and pragmatic errors. The subjects of this research are Indonesian EFL learners, students in Muhammadiyah University of Surakarta. The researcher took the subject base on the length of study, there are three levels: second semester (ScS); fourth semester (FS); and sixth semester (SS). The data of this research are errors in grammar and pragmatic. The data source obtained from the result of questionnaire. The method of collecting data is questionnaire (DCT) and interview. In analyzing the data, the writer will put his greatest concern Leech's pragmatics theory (1983) pragmalinguistic and sociopragmatic. Based on the 75 participants and 10 questions of DCT there are 750 data of errors. This research shows that firstly: there were 381 data shows grammar error (50,8%), 281 shows pragmatic errors (37,47%), 64 shows that both of them errors (8,53%) and 24 did not identifying the errors (3,2%). Secondly, the length of study influence the understanding of grammar and pragmatic errors, but the length of study can't be the measure of the knowledge. Thirdly, the kind of errors that often found by learners is grammar error. They can explain details about grammatical error, but on pragmatic error they are only explain based on social class. It means that, the result of this research is the Indonesian EFL learners were more aware grammar error than pragmatic error.